Răspunsuri

2014-04-28T12:05:24+03:00
Ai ca x = ( 60  /100 ) * y => x = ( 3 / 5 )*y => y = ( 5 / 3)*x;

Atunci y / (x + y) = p / 100 <=> ( 5 / 3)*x / [ x + ( 5 / 3)*x ] = p / 100 <=> 
 ( 5 / 3)*x / (  8 / 3)*x = p / 100 <=> 5 / 8 = p / 100 <=> p = 800 / 5 <=> p = 160 => 160%;

y / ( y - x ) = p / 100 <=>  ( 5 / 3)*x / ( 2 / 3)*x = p / 100 <=> 5 / 2 = p / 100 <=> p = 250 => p = 250%;


Bafta!
In mod corect avem ca 5 / 8 = p / 100 => p = 500 / 8 => p = 62.5 => y reprezinta 62.5& din x + y si, printr- un calcul analog obtii ca y reprezinta 40% din y -x !